SlideShare a Scribd company logo
1 of 6
Kumera Nemomsa
Part I
a).Let's evaluate the statement for each possible combination:
For x = 1:
For y = 1: 1^2 + 2(1) = 3 < 10 (True)
For y = 2: 1^2 + 2(2) = 5 < 10 (True)
For y = 3: 1^2 + 2(3) = 7 < 10 (True)
For x = 2:
For y = 1: 2^2 + 2(1) = 6 < 10 (True)
For y = 2: 2^2 + 2(2) = 10 < 10 (False)
For y = 3: 2^2 + 2(3) = 14 < 10 (False)
Since we found some combinations of x and y where the statement is false, the overall truth
value of (∀x)(∀y)(x^2+2y<10) is false.
In other words, there exist values of x and y within the given set u = {1, 2, 3} for which the
expression x^2 + 2y is greater than or equal to 10.
b).Let's evaluate the statement for each value of x:
For x = 1:
For y = 1: 1^2 + 2(1) = 3 < 10 (True)
For y = 2: 1^2 + 2(2) = 5 < 10 (True)
For y = 3: 1^2 + 2(3) = 7 < 10 (True)
Since the inequality holds true for all values of y when x = 1, we can conclude that (∃x)(∀y)(x^2
+ 2y < 10) is true for x = 1.
Therefore, the statement (∃x)(∀y)(x^2 + 2y < 10) is true for the given set u = {1, 2, 3} because
there exists at least one value of x (in this case, x = 1) for which the inequality holds true for all
values of y within the set.
c).
Let's evaluate the statement for each value of x:
For x = 1:
For y = 1: 1^2 + 2(1) = 3 < 10 (True)
For y = 2: 1^2 + 2(2) = 5 < 10 (True)
For y = 3: 1^2 + 2(3) = 7 < 10 (True)
Since the inequality holds true for all values of y when x = 1, we can conclude that (∃x)(∀y)(x^2
+ 2y < 10) is true for x = 1.
Therefore, the statement (∃x)(∀y)(x^2 + 2y < 10) is true for the given set u = {1, 2, 3} because
there exists at least one value of x (in this case, x = 1) for which the inequality holds true for all
values of y within the set.
d).
Let's evaluate the statement for each combination of x and y:
For x = 1:
For y = 0: 1^2 + 2(0) = 1 < 10 (True)
For y = 1: 1^2 + 2(1) = 3 < 10 (True)
For y = 2: 1^2 + 2(2) = 5 < 10 (True)
For y = 3: 1^2 + 2(3) = 7 < 10 (True)
For x = 2:
For y = 0: 2^2 + 2(0) = 4 < 10 (True)
For y = 1: 2^2 + 2(1) = 6 < 10 (True)
For y = 2: 2^2 + 2(2) = 8 < 10 (True)
For y = 3: 2^2 + 2(3) = 10 < 10 (False)
Since there exist values of x and y within the set u = {1, 2, 3} for which the inequality x^2 + 2y <
10 holds true, the statement (∃x)(∃y)(x^2 + 2y < 10) is true.
In other words, there exists at least one pair of values (x, y) within the set u such that the
expression x^2 + 2y is less than 10, which means the statement (∃x)(∃y)(x^2 + 2y < 10) is true.
Part II
Prove the Validity of the argument
a).
To prove the validity of the argument:
Premise 1: (p → q) ∧ (r → s)
Premise 2: p ∨ r
Conclusion: ¬q → s
We can use deductive reasoning and logical rules to demonstrate the validity of the argument.
Here's a proof:
Assume ¬q (Assumption for Conditional Proof)
Assume ¬s (Assumption for Conditional Proof)
From premise 1, (p → q) ∧ (r → s), we have p → q (Simplification)
From premise 2, p ∨ r, we have two cases to consider:
4.1. Case 1: Assume p
4.1.1. From ¬q (assumption), we derive a contradiction: ¬q and q (Contradiction Introduction)
4.1.2. As a contradiction has been reached, we can conclude that the assumption p is false
(Proof by contradiction)
4.2. Case 2: Assume r
4.2.1. From r → s (premise 1) and r (assumption), we can conclude s (Modus Ponens)
Since in both cases, either p or r leads to a contradiction, we can conclude that both p and r are
false (Disjunctive Syllogism)
Since p is false, we can conclude ¬p (Negation Introduction)
Since ¬p and ¬q, we have ¬p ∧ ¬q (Conjunction Introduction)
Using De Morgan's law, we can rewrite the conjunction as ¬(p ∨ q) (De Morgan's Law)
From ¬(p ∨ q), we can derive p ∨ q (Double Negation)
From p ∨ q, we have q (Disjunctive Syllogism)
From q and ¬q, we have a contradiction: q and ¬q (Contradiction Introduction)
As a contradiction has been reached, our initial assumption ¬q must be false (Proof by
contradiction)
Therefore, we can conclude ¬q → s (Conditional Proof: ¬q → s)
Therefore, the argument is valid as we have shown that the conclusion ¬q → s logically follows
from the premises.
By going through this proof, we have demonstrated that if the premises (p → q) ∧ (r → s) and p
∨ r hold, then the conclusion ¬q → s is necessarily true. Hence, the argument is valid.
b).
To prove the validity of the argument:
Premise 1: p → q
Premise 2: ¬p → r
Premise 3: r → s
Conclusion: ¬q → s
We can use deductive reasoning and logical rules to demonstrate the validity of the argument.
Here's a proof:
Assume ¬q (Assumption for Conditional Proof)
From premise 1, p → q, and the assumption ¬q, we can conclude ¬p (Modus Tollens)
From premise 2, ¬p → r, and ¬p (derived from step 2), we can conclude r (Modus Ponens)
From premise 3, r → s, and r (derived from step 3), we can conclude s (Modus Ponens)
Therefore, from the assumption ¬q, we have derived s
Thus, ¬q → s (Conditional Proof)
Therefore, the argument is valid as we have shown that the conclusion ¬q → s logically follows
from the premises.
By going through this proof, we have demonstrated that if the premises p → q, ¬p → r, and r →
s hold, then the conclusion ¬q → s is necessarily true. Hence, the argument is valid.
c).
To prove the validity of the argument:
Premise 1: (¬p ∧ ¬q)
Premise 2: (q ∨ r) → p
Conclusion: ¬r
We can use deductive reasoning and logical rules to demonstrate the validity of the argument.
Here's a proof:
Assume r (Assumption for Conditional Proof)
From Premise 2, we have (q ∨ r) → p
Since we assumed r, we can conclude (q ∨ r) (Addition)
From (q ∨ r) → p and (q ∨ r) (derived from steps 2 and 3), we can conclude p (Modus Ponens)
From Premise 1, we have (¬p ∧ ¬q)
From (¬p ∧ ¬q), we have ¬p (Simplification)
From p and ¬p, we have a contradiction: p and ¬p (Contradiction Introduction)
As a contradiction has been reached, our initial assumption r must be false (Proof by
contradiction)
Therefore, ¬r (Negation Introduction)
Therefore, the argument is valid as we have shown that the conclusion ¬r logically follows from
the premises.
By going through this proof, we have demonstrated that if the premises (¬p ∧ ¬q) and (q ∨ r) →
p hold, then the conclusion ¬r is necessarily true. Hence, the argument is valid.
d).
To prove the validity of the argument:
Premise 1: ¬r ∧ ¬s
Premise 2: (¬s → p) → r
Conclusion: ¬p
We can use deductive reasoning and logical rules to demonstrate the validity of the argument.
Here's a proof:
Assume p (Assumption for Conditional Proof)
From Premise 2, (¬s → p) → r, and the assumption p, we can conclude r (Modus Ponens)
From Premise 1, ¬r ∧ ¬s, we have ¬r (Simplification)
From ¬r and r, we have a contradiction: ¬r and r (Contradiction Introduction)
As a contradiction has been reached, our initial assumption p must be false (Proof by
contradiction)
Therefore, ¬p (Negation Introduction)
Therefore, the argument is valid as we have shown that the conclusion ¬p logically follows from
the premises.By going through this proof, we have demonstrated that if the premises ¬r ∧ ¬s
and (¬s → p) → r hold, then the conclusion ¬p is necessarily true. Hence, the argument is valid.

More Related Content

Similar to Kumera2.docx

Prin digcommselectedsoln
Prin digcommselectedsolnPrin digcommselectedsoln
Prin digcommselectedsoln
Ahmed Alshomi
 
HypergroupsAssociationSchemes_leejuntaek
HypergroupsAssociationSchemes_leejuntaekHypergroupsAssociationSchemes_leejuntaek
HypergroupsAssociationSchemes_leejuntaek
Jun Taek Lee
 
Discrete-Chapter 05 Inference and Proofs
Discrete-Chapter 05 Inference and ProofsDiscrete-Chapter 05 Inference and Proofs
Discrete-Chapter 05 Inference and Proofs
Wongyos Keardsri
 
New Pythagorean Triples copy
New Pythagorean Triples copyNew Pythagorean Triples copy
New Pythagorean Triples copy
Andrew Erskine
 
The Application of Derivatives
The Application of DerivativesThe Application of Derivatives
The Application of Derivatives
divaprincess09
 

Similar to Kumera2.docx (20)

Theoryofcomp science
Theoryofcomp scienceTheoryofcomp science
Theoryofcomp science
 
Probable
ProbableProbable
Probable
 
Northcott1957 (1)
Northcott1957 (1)Northcott1957 (1)
Northcott1957 (1)
 
Proof of Beal's conjecture
Proof of Beal's conjecture Proof of Beal's conjecture
Proof of Beal's conjecture
 
Prin digcommselectedsoln
Prin digcommselectedsolnPrin digcommselectedsoln
Prin digcommselectedsoln
 
Induction.pdf
Induction.pdfInduction.pdf
Induction.pdf
 
Proving existential statements
Proving existential statementsProving existential statements
Proving existential statements
 
02 asymptotic notations
02 asymptotic notations02 asymptotic notations
02 asymptotic notations
 
Appendix to MLPI Lecture 2 - Monte Carlo Methods (Basics)
Appendix to MLPI Lecture 2 - Monte Carlo Methods (Basics)Appendix to MLPI Lecture 2 - Monte Carlo Methods (Basics)
Appendix to MLPI Lecture 2 - Monte Carlo Methods (Basics)
 
asymptotic notations i
asymptotic notations iasymptotic notations i
asymptotic notations i
 
Mcs 013 solve assignment
Mcs 013 solve assignmentMcs 013 solve assignment
Mcs 013 solve assignment
 
PROOF TECHNIQUES
PROOF TECHNIQUESPROOF TECHNIQUES
PROOF TECHNIQUES
 
HypergroupsAssociationSchemes_leejuntaek
HypergroupsAssociationSchemes_leejuntaekHypergroupsAssociationSchemes_leejuntaek
HypergroupsAssociationSchemes_leejuntaek
 
Orthogonal basis and gram schmidth process
Orthogonal basis and gram schmidth processOrthogonal basis and gram schmidth process
Orthogonal basis and gram schmidth process
 
Discrete-Chapter 05 Inference and Proofs
Discrete-Chapter 05 Inference and ProofsDiscrete-Chapter 05 Inference and Proofs
Discrete-Chapter 05 Inference and Proofs
 
Factorials as sums
Factorials as sumsFactorials as sums
Factorials as sums
 
Ijetr021233
Ijetr021233Ijetr021233
Ijetr021233
 
Math Assignment Help
Math Assignment HelpMath Assignment Help
Math Assignment Help
 
New Pythagorean Triples copy
New Pythagorean Triples copyNew Pythagorean Triples copy
New Pythagorean Triples copy
 
The Application of Derivatives
The Application of DerivativesThe Application of Derivatives
The Application of Derivatives
 

Recently uploaded

audience research (emma) 1.pptxkkkkkkkkkkkkkkkkk
audience research (emma) 1.pptxkkkkkkkkkkkkkkkkkaudience research (emma) 1.pptxkkkkkkkkkkkkkkkkk
audience research (emma) 1.pptxkkkkkkkkkkkkkkkkk
lolsDocherty
 
Production 2024 sunderland culture final - Copy.pptx
Production 2024 sunderland culture final - Copy.pptxProduction 2024 sunderland culture final - Copy.pptx
Production 2024 sunderland culture final - Copy.pptx
ChloeMeadows1
 

Recently uploaded (17)

Bug Bounty Blueprint : A Beginner's Guide
Bug Bounty Blueprint : A Beginner's GuideBug Bounty Blueprint : A Beginner's Guide
Bug Bounty Blueprint : A Beginner's Guide
 
GOOGLE Io 2024 At takes center stage.pdf
GOOGLE Io 2024 At takes center stage.pdfGOOGLE Io 2024 At takes center stage.pdf
GOOGLE Io 2024 At takes center stage.pdf
 
I’ll See Y’All Motherfuckers In Game 7 Shirt
I’ll See Y’All Motherfuckers In Game 7 ShirtI’ll See Y’All Motherfuckers In Game 7 Shirt
I’ll See Y’All Motherfuckers In Game 7 Shirt
 
audience research (emma) 1.pptxkkkkkkkkkkkkkkkkk
audience research (emma) 1.pptxkkkkkkkkkkkkkkkkkaudience research (emma) 1.pptxkkkkkkkkkkkkkkkkk
audience research (emma) 1.pptxkkkkkkkkkkkkkkkkk
 
Production 2024 sunderland culture final - Copy.pptx
Production 2024 sunderland culture final - Copy.pptxProduction 2024 sunderland culture final - Copy.pptx
Production 2024 sunderland culture final - Copy.pptx
 
Free scottie t shirts Free scottie t shirts
Free scottie t shirts Free scottie t shirtsFree scottie t shirts Free scottie t shirts
Free scottie t shirts Free scottie t shirts
 
Pvtaan Social media marketing proposal.pdf
Pvtaan Social media marketing proposal.pdfPvtaan Social media marketing proposal.pdf
Pvtaan Social media marketing proposal.pdf
 
TORTOGEL TELAH MENJADI SALAH SATU PLATFORM PERMAINAN PALING FAVORIT.
TORTOGEL TELAH MENJADI SALAH SATU PLATFORM PERMAINAN PALING FAVORIT.TORTOGEL TELAH MENJADI SALAH SATU PLATFORM PERMAINAN PALING FAVORIT.
TORTOGEL TELAH MENJADI SALAH SATU PLATFORM PERMAINAN PALING FAVORIT.
 
Statistical Analysis of DNS Latencies.pdf
Statistical Analysis of DNS Latencies.pdfStatistical Analysis of DNS Latencies.pdf
Statistical Analysis of DNS Latencies.pdf
 
The Use of AI in Indonesia Election 2024: A Case Study
The Use of AI in Indonesia Election 2024: A Case StudyThe Use of AI in Indonesia Election 2024: A Case Study
The Use of AI in Indonesia Election 2024: A Case Study
 
iThome_CYBERSEC2024_Drive_Into_the_DarkWeb
iThome_CYBERSEC2024_Drive_Into_the_DarkWebiThome_CYBERSEC2024_Drive_Into_the_DarkWeb
iThome_CYBERSEC2024_Drive_Into_the_DarkWeb
 
Reggie miller choke t shirtsReggie miller choke t shirts
Reggie miller choke t shirtsReggie miller choke t shirtsReggie miller choke t shirtsReggie miller choke t shirts
Reggie miller choke t shirtsReggie miller choke t shirts
 
Thank You Luv I’ll Never Walk Alone Again T shirts
Thank You Luv I’ll Never Walk Alone Again T shirtsThank You Luv I’ll Never Walk Alone Again T shirts
Thank You Luv I’ll Never Walk Alone Again T shirts
 
Development Lifecycle.pptx for the secure development of apps
Development Lifecycle.pptx for the secure development of appsDevelopment Lifecycle.pptx for the secure development of apps
Development Lifecycle.pptx for the secure development of apps
 
Cyber Security Services Unveiled: Strategies to Secure Your Digital Presence
Cyber Security Services Unveiled: Strategies to Secure Your Digital PresenceCyber Security Services Unveiled: Strategies to Secure Your Digital Presence
Cyber Security Services Unveiled: Strategies to Secure Your Digital Presence
 
Premier Mobile App Development Agency in USA.pdf
Premier Mobile App Development Agency in USA.pdfPremier Mobile App Development Agency in USA.pdf
Premier Mobile App Development Agency in USA.pdf
 
How Do I Begin the Linksys Velop Setup Process?
How Do I Begin the Linksys Velop Setup Process?How Do I Begin the Linksys Velop Setup Process?
How Do I Begin the Linksys Velop Setup Process?
 

Kumera2.docx

  • 1. Kumera Nemomsa Part I a).Let's evaluate the statement for each possible combination: For x = 1: For y = 1: 1^2 + 2(1) = 3 < 10 (True) For y = 2: 1^2 + 2(2) = 5 < 10 (True) For y = 3: 1^2 + 2(3) = 7 < 10 (True) For x = 2: For y = 1: 2^2 + 2(1) = 6 < 10 (True) For y = 2: 2^2 + 2(2) = 10 < 10 (False) For y = 3: 2^2 + 2(3) = 14 < 10 (False) Since we found some combinations of x and y where the statement is false, the overall truth value of (∀x)(∀y)(x^2+2y<10) is false. In other words, there exist values of x and y within the given set u = {1, 2, 3} for which the expression x^2 + 2y is greater than or equal to 10. b).Let's evaluate the statement for each value of x: For x = 1: For y = 1: 1^2 + 2(1) = 3 < 10 (True) For y = 2: 1^2 + 2(2) = 5 < 10 (True) For y = 3: 1^2 + 2(3) = 7 < 10 (True)
  • 2. Since the inequality holds true for all values of y when x = 1, we can conclude that (∃x)(∀y)(x^2 + 2y < 10) is true for x = 1. Therefore, the statement (∃x)(∀y)(x^2 + 2y < 10) is true for the given set u = {1, 2, 3} because there exists at least one value of x (in this case, x = 1) for which the inequality holds true for all values of y within the set. c). Let's evaluate the statement for each value of x: For x = 1: For y = 1: 1^2 + 2(1) = 3 < 10 (True) For y = 2: 1^2 + 2(2) = 5 < 10 (True) For y = 3: 1^2 + 2(3) = 7 < 10 (True) Since the inequality holds true for all values of y when x = 1, we can conclude that (∃x)(∀y)(x^2 + 2y < 10) is true for x = 1. Therefore, the statement (∃x)(∀y)(x^2 + 2y < 10) is true for the given set u = {1, 2, 3} because there exists at least one value of x (in this case, x = 1) for which the inequality holds true for all values of y within the set. d). Let's evaluate the statement for each combination of x and y: For x = 1: For y = 0: 1^2 + 2(0) = 1 < 10 (True) For y = 1: 1^2 + 2(1) = 3 < 10 (True) For y = 2: 1^2 + 2(2) = 5 < 10 (True) For y = 3: 1^2 + 2(3) = 7 < 10 (True) For x = 2: For y = 0: 2^2 + 2(0) = 4 < 10 (True) For y = 1: 2^2 + 2(1) = 6 < 10 (True) For y = 2: 2^2 + 2(2) = 8 < 10 (True) For y = 3: 2^2 + 2(3) = 10 < 10 (False)
  • 3. Since there exist values of x and y within the set u = {1, 2, 3} for which the inequality x^2 + 2y < 10 holds true, the statement (∃x)(∃y)(x^2 + 2y < 10) is true. In other words, there exists at least one pair of values (x, y) within the set u such that the expression x^2 + 2y is less than 10, which means the statement (∃x)(∃y)(x^2 + 2y < 10) is true. Part II Prove the Validity of the argument a). To prove the validity of the argument: Premise 1: (p → q) ∧ (r → s) Premise 2: p ∨ r Conclusion: ¬q → s We can use deductive reasoning and logical rules to demonstrate the validity of the argument. Here's a proof: Assume ¬q (Assumption for Conditional Proof) Assume ¬s (Assumption for Conditional Proof) From premise 1, (p → q) ∧ (r → s), we have p → q (Simplification) From premise 2, p ∨ r, we have two cases to consider: 4.1. Case 1: Assume p 4.1.1. From ¬q (assumption), we derive a contradiction: ¬q and q (Contradiction Introduction) 4.1.2. As a contradiction has been reached, we can conclude that the assumption p is false (Proof by contradiction) 4.2. Case 2: Assume r 4.2.1. From r → s (premise 1) and r (assumption), we can conclude s (Modus Ponens)
  • 4. Since in both cases, either p or r leads to a contradiction, we can conclude that both p and r are false (Disjunctive Syllogism) Since p is false, we can conclude ¬p (Negation Introduction) Since ¬p and ¬q, we have ¬p ∧ ¬q (Conjunction Introduction) Using De Morgan's law, we can rewrite the conjunction as ¬(p ∨ q) (De Morgan's Law) From ¬(p ∨ q), we can derive p ∨ q (Double Negation) From p ∨ q, we have q (Disjunctive Syllogism) From q and ¬q, we have a contradiction: q and ¬q (Contradiction Introduction) As a contradiction has been reached, our initial assumption ¬q must be false (Proof by contradiction) Therefore, we can conclude ¬q → s (Conditional Proof: ¬q → s) Therefore, the argument is valid as we have shown that the conclusion ¬q → s logically follows from the premises. By going through this proof, we have demonstrated that if the premises (p → q) ∧ (r → s) and p ∨ r hold, then the conclusion ¬q → s is necessarily true. Hence, the argument is valid. b). To prove the validity of the argument: Premise 1: p → q Premise 2: ¬p → r Premise 3: r → s Conclusion: ¬q → s We can use deductive reasoning and logical rules to demonstrate the validity of the argument. Here's a proof: Assume ¬q (Assumption for Conditional Proof) From premise 1, p → q, and the assumption ¬q, we can conclude ¬p (Modus Tollens) From premise 2, ¬p → r, and ¬p (derived from step 2), we can conclude r (Modus Ponens) From premise 3, r → s, and r (derived from step 3), we can conclude s (Modus Ponens) Therefore, from the assumption ¬q, we have derived s
  • 5. Thus, ¬q → s (Conditional Proof) Therefore, the argument is valid as we have shown that the conclusion ¬q → s logically follows from the premises. By going through this proof, we have demonstrated that if the premises p → q, ¬p → r, and r → s hold, then the conclusion ¬q → s is necessarily true. Hence, the argument is valid. c). To prove the validity of the argument: Premise 1: (¬p ∧ ¬q) Premise 2: (q ∨ r) → p Conclusion: ¬r We can use deductive reasoning and logical rules to demonstrate the validity of the argument. Here's a proof: Assume r (Assumption for Conditional Proof) From Premise 2, we have (q ∨ r) → p Since we assumed r, we can conclude (q ∨ r) (Addition) From (q ∨ r) → p and (q ∨ r) (derived from steps 2 and 3), we can conclude p (Modus Ponens) From Premise 1, we have (¬p ∧ ¬q) From (¬p ∧ ¬q), we have ¬p (Simplification) From p and ¬p, we have a contradiction: p and ¬p (Contradiction Introduction) As a contradiction has been reached, our initial assumption r must be false (Proof by contradiction) Therefore, ¬r (Negation Introduction) Therefore, the argument is valid as we have shown that the conclusion ¬r logically follows from the premises. By going through this proof, we have demonstrated that if the premises (¬p ∧ ¬q) and (q ∨ r) → p hold, then the conclusion ¬r is necessarily true. Hence, the argument is valid. d).
  • 6. To prove the validity of the argument: Premise 1: ¬r ∧ ¬s Premise 2: (¬s → p) → r Conclusion: ¬p We can use deductive reasoning and logical rules to demonstrate the validity of the argument. Here's a proof: Assume p (Assumption for Conditional Proof) From Premise 2, (¬s → p) → r, and the assumption p, we can conclude r (Modus Ponens) From Premise 1, ¬r ∧ ¬s, we have ¬r (Simplification) From ¬r and r, we have a contradiction: ¬r and r (Contradiction Introduction) As a contradiction has been reached, our initial assumption p must be false (Proof by contradiction) Therefore, ¬p (Negation Introduction) Therefore, the argument is valid as we have shown that the conclusion ¬p logically follows from the premises.By going through this proof, we have demonstrated that if the premises ¬r ∧ ¬s and (¬s → p) → r hold, then the conclusion ¬p is necessarily true. Hence, the argument is valid.